Conjugated Conduction-Free Convection Heat Transfer in an Annulus Heated at Either Constant Wall Temperature or Constant Heat Flux - HAROON IMTIAZ; FATHI MOHAMAD MAHFOUZ (Mehran University Research Journal of Engineering and Technology, 2017)
In this paper, we investigate numerically the effect of thermal boundary conditions on conjugated conduction-free convection heat transfer in an annulus between two concentric cylinders using Fourier Spectral method. The inner wall of the annulus is heated and maintained at either CWT (Constant Wall Temperature) or CHF (Constant Heat Flux), while the outer wall is maintained at constant temperature. CHF case is relatively more significant for high pressure industrial applications, but it has not received much attention. This study particularly focuses the latter case (CHF). The main influencing parameters on flow and thermal fields within the annulus are: Rayleigh number Ra; thickness of inner wall Rs; radius ratio Rr and inner wall-fluid thermal conductivity ratio Kr. The study has shown that the increase in Kr increases the heat transfer rate through the annulus for heating at CWT and decreases the inner wall dimensionless temperature for heating at CHF and vice versa. It has also been proved that as the Rs increases at fixed Ra and Rr, the heat transfer rate decreases for heating at CWT and the inner wall dimensionless temperature increases for heating at CHF at Kr 1 depends on Rr. It has been shown that for certain combinations of controlling parameters there will be a value of Rr at which heat transfer rate will be minimum in the annulus in case of heating at CWT, while